2020
DOI: 10.1192/j.eurpsy.2020.66
|View full text |Cite
|
Sign up to set email alerts
|

Emotional intelligence in bipolar-I-disorder: A comparison between patients, unaffected siblings, and control subjects

Abstract: Background. Impairments in social and nonsocial cognition have been demonstrated in both patients suffering from bipolar disorder (BD) and their unaffected relatives and might therefore represent a heritable marker of risk. This study investigated the relevance of emotional intelligence (EI) as part of the emotion processing domain of social cognition in this regard. Methods. A total of 54 outpatients suffering from BD, 54 unaffected siblings, and 80 control subjects were investigated us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
(48 reference statements)
1
8
0
Order By: Relevance
“…Regarding sex differences in EI, our findings are in line with previous studies in which men performed worse than women on EI in non-clinical samples (Pardeller, Frajo-Apor, Kemmler, & Hofer, 2017) and BD patients (Varo et al, 2019). As for the role played by verbal memory in EI, our finding is in line with previous literature underlining how EI performance might be associated with cognitive abilities (Eack et al, 2010; Frajo-Apor et al, 2020; Varo et al, 2019). In a previous study assessing BD patients, all neurocognitive domains were associated with EI (Varo et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Regarding sex differences in EI, our findings are in line with previous studies in which men performed worse than women on EI in non-clinical samples (Pardeller, Frajo-Apor, Kemmler, & Hofer, 2017) and BD patients (Varo et al, 2019). As for the role played by verbal memory in EI, our finding is in line with previous literature underlining how EI performance might be associated with cognitive abilities (Eack et al, 2010; Frajo-Apor et al, 2020; Varo et al, 2019). In a previous study assessing BD patients, all neurocognitive domains were associated with EI (Varo et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Although EI has been widely studied in patients in later stages of BD (Aparicio et al, 2017; Frajo-Apor et al, 2020; Samamé et al, 2015; Varo et al, 2019), little is known about the EI performance of patients after a FEM and the course of EI impairment across the clinical stages of BD and the evidence is seldom conflicting. So far, only two studies assessed some level of EI patients after a FEM (Daros et al, 2014; Szmulewicz et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding may indicate that the managing emotion ability is the most impacted subdomain of emotional intelligence in the patients suffering from BD. The performance in the managing emotions branch typically predicts a majority of mental disorders, such as schizophrenia ( 58 ) and bipolar disorder, compared to unaffected siblings ( 59 ). In the current study, we found that the difference in the managing emotions scores of the MSCEIT between the BD epi and BD eut groups remained significant, implying that the ability to manage emotions could be mood-dependent and a state-like marker for the evaluation of the progressive course of the illness.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the early detection of a potential endo-phenotype of bipolar spectrum disorder is important due to the clinical implications, and may be used in monitoring the progression of the disorder ( 59 ). Thus far, no effect of subtypes on EI performance was noted; however, the disorder course had a greater impact instead.…”
Section: Discussionmentioning
confidence: 99%